Successful defibrillation verification in subcutaneous implantable cardioverter‐defibrillator recipients by low‐energy shocks - Biffi, Mauro (Clin Cardiol, 2019)
BACKGROUND: The subcutaneous implantable cardioverter‐defibrillator (S‐ICD) is an effective alternative to the transvenous one. Defibrillation efficacy depends on maximum device output and on the optimal device location at device implantation. HYPOTHESIS: We sought to investigate the defibrillation safety margin in real life clinical practice. METHODS: We sought to understand what is the efficacy of induced ventricular fibrillation (VF) termination at S‐ICD implantation using lower energies than the recommended 65 J. RESULTS: Sixty‐four consecutive S‐ICD recipients underwent VF termination attempts at implantation with energies ranging from 20 to 50 J. Overall, VF termination occurred in 84% of patients with ≤40 J, in 88% with 45 J, and in 100% with 60 J. Intermuscular S‐ICD placement was associated with 94% VF termination at ≤40 J. An ejection fraction <35% was associated to higher energy requirement for defibrillation; however, an intermuscular S‐ICD placement conferred 90% defibrillation efficacy at 31 ± 5 J in this patients subset. CONCLUSIONS: This is a hypothesis‐generating observation that prompts a methodologically correct investigation to prove that a 60 J output S‐ICD can provide an adequate safety margin to terminate VF in clinical practice. This would enable superior device longevity and/or device downsizing for pediatric/small size patients.